Linking xylem water storage with anatomical parameters in five temperate tree species - Jupa, Radek; Plavcová, Lenka; Gloser, Vít; Jansen, Steven (Tree physiology, 2016)
The release of water from storage compartments to the transpiration stream is an important functional mechanism that provides the buffering of sudden fluctuations in water potential. The ability of tissues to release water per change in water potential, referred to as hydraulic capacitance, is assumed to be associated with the anatomy of storage tissues. However, information about how specific anatomical parameters determine capacitance is limited. In this study, we measured sapwood capacitance (C) in terminal branches and roots of five temperate tree species (Fagus sylvatica L., Picea abies L., Quercus robur L., Robinia pseudoacacia L., Tilia cordata Mill.). Capacitance was calculated separately for water released mainly from capillary (CI; open vessels, tracheids, fibres, intercellular spaces and cracks) and elastic storage compartments (CII; living parenchyma cells), corresponding to two distinct phases of the moisture release curve. We found that C was generally higher in roots than branches, with CI being 3-11 times higher than CII Sapwood density and the ratio of dead to living xylem cells were most closely correlated with C In addition, the magnitude of CI was strongly correlated with fibre/tracheid lumen area, whereas CII was highly dependent on the thickness of axial parenchyma cell walls. Our results indicate that water released from capillary compartments predominates over water released from elastic storage in both branches and roots, suggesting the limited importance of parenchyma cells for water storage in juvenile xylem of temperate tree species. Contrary to intact organs, water released from open conduits in our small wood samples significantly increased CI at relatively high water potentials. Linking anatomical parameters with the hydraulic capacitance of a tissue contributes to a better understanding of water release mechanisms and their implications for plant hydraulics.
Keywords: Wood; capacitance; embolism; stromy; parenchyma; root xylem; Water; Trees; Xylem; water potential; branch xylem; wood density; sapwood; voda; dřevo; xylém